Vademécum urbanístico y la efectividad de procesos constructivos: Urbanización Sotileza, Isla Mocolí, Ecuador - Charcopa Arias, María Cristina (2022)
The objective of the research project is the analysis of construction processes in an urbanization with the purpose of proposing the realization of a Vademécum, which compiles efficient and effective procedures of construction activities based on current construction regulations and the work experience of engineers, architects and construction managers. The study project is located in the Samborondón canton of the La Puntilla Satellite Parish - Mocolí Island, which has an area of 10.30 hectares in the South West Point of the Island, through data collection we were able to observe the possibility of improvements in the application of more agile construction procedures and optimizing resources allowing to increase the profitability of the project under study and used as a guiding instrument for professionals in training and professionals from other branches of engineering and students.....